Dynamic correlation between chest temperature entropy and physiological load indicators, and excess post-exercise oxygen consumption during incremental cycling exercise - Cui, Songzi; Du, Ning; Liu, Zhongqian; Hu, Chenxi (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to investigate the dynamic relationship between chest temperature entropy, physiological load indicators, and excess post-exercise oxygen consumption (EPOC) during incremental cycling exercise using high-sampling-rate infrared thermography (IRT).MethodsTwenty-four healthy young male participants (23.7 ± 3.3 years; 178.6 ± 9.8 cm; 78.5 ± 6.4 kg; 237.8 ± 48.7 min/week training duration; maximal oxygen uptake 44.06 ± 5.9 ml/kg/min; maximal power output 263.8 ± 27.4 W) performed an incremental cycling test starting at 60 W with workload increases of 30 W every 2 minutes until exhaustion. Chest thermography, oxygen consumption (VO₂), blood lactate, and external load were simultaneously measured, and entropy was used to quantify the spatial complexity of temperature distribution.ResultsSignificant non-linear positive correlations were found between standardized entropy increase and VO₂ (R² = 0.809), blood lactate (R² = 0.719), and external load (R² = 0.841), while individual-level analyses confirmed strong associations with VO₂ (r = 0.874–0.977), lactate (r = 0.692–0.989), and external load (r = 0.889–0.986) (all p < 0.05). Hierarchical clustering identified three clusters corresponding to low, moderate, and high metabolic load states. During recovery, entropy was significantly associated with EPOC (R² = 0.151), though substantial inter-individual variation was observed (r = –0.288 to 0.907).ConclusionChest temperature entropy dynamically reflects exercise-induced metabolic changes and partially explains recovery processes, highlighting its potential as a novel, non-invasive marker for monitoring exercise load and recovery.